Human amniotic fluid derived extracellular vesicles attenuate T cell immune response - del Rivero, Tania; Milberg, Julian; Bennett, Cassie; Mitrani, Maria Ines; Bellio, Michael A. (Frontiers in Immunology, 2022)
Extracellular vesicles isolated from human amniotic fluid (AF-EVs) have previously been found to modulate inflammation and macrophage infiltration in a mouse model. However, the effects of acellular amniotic fluid (acAF) or AF-EVs on the T-Cell immune response have not been explored. In thisese studyies, we investigated the effects of acAF and AF-EVs on the T cell immune response in an in vitro cell culture model. Peripheral Blood Mononuclear Cells (PBMCs) were stimulated with Phytohemagglutinin (PHA) to induce the immune response and were subsequently treated with either serum-free media (vehicle), acAF, or concentrated AF-EVs. Both acAF and AF-EV treatment suppressed PHA-induced T cell proliferation and PHA-induced T cell activation; however, treatment with concentrated AF-EVs had a greater effect. Additionally, both acAF and AF-EVs reduced PBMC pro-inflammatory cytokine release. AF-EVs were found to be taken up by both CD4+ and CD8+ effector T cell subsets. Overall, this data demonstrates that AF-EVs have a robust immunomodulatory effect on T cells and suggests AF-EVs could be used as an immunotherapeutic tool.